Low‐Power, Multi‐Transduction Nanosensor Array for Accurate Sensing of Flammable and Toxic Gases (Small Methods 3/2023). Issue 3 (13th March 2023) - Henriquez, Dionisio V. Del Orbe; Kang, Mingu; Cho, Incheol; Choi, Jungrak; Park, Jaeho; Gul, Osman; Ahn, Junseong; Lee, Dae‐Sik; Park, Inkyu
Abstract : Inside Back Cover In article number 2201352, Lee, Park, and co‐workers demonstrated a low‐power, multi‐transduction nanosensor array by integrating nanostructured materials on bridge‐type microheaters for accurate gas sensing. By using various responses of the nanosensor array based on chemiresistive and calorimetric mechanisms, it is possible to accurately identify flammable and toxic gases in real‐time.